2010
DOI: 10.5713/ajas.2010.10077
|View full text |Cite
|
Sign up to set email alerts
|

Intermediary Metabolism of Plasma Acetic Acid, Glucose and Protein in Sheep Fed a Rice Straw-based Diet

Abstract: The present study was conducted to determine plasma acetate, glucose and protein metabolism using dilution of isotopes [[1-13 C]Na acetate, [U-13 C]glucose and [1-13 C]leucine (Leu)] in sheep fed rice straw (Oriza japonica L.). Four sheep were assigned to either rice straw (RS-diet) or mixed hay (MH-diet) with a crossover design. Nitrogen (N) intake and N digestibility were lower (p = 0.002 and p = 0.02, respectively) for RS-diet than MH-diet, but N retention did not differ (p>0.10) between the diets. Concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
4
8
1
2
Order By: Relevance
“…In our study, the N intake of sheep in the CD 2% and CD 4% groups was higher than that in the control group, and N egestion in feces had no significant difference between addition groups and control group, indicating higher N digestibility in the CD 2% and CD 4% groups compared with that in the control group. The results agree with the previous studies [27], which showed that increased CP intake resulted in enhanced N digestibility and elevated urinary N excretion in sheep [28], and this may be explained the hydrolysis of plant additives in rumen and reduced complex formation with protein, resulting in increased nitrogen through urine [29]. Retained nitrogen had an increasing tendency in C. deserticola addition group, so during the experimental period, sheep in all addition groups were in positive nitrogen balance; these results were the same as the studies on the impact of phytogenic feed additives on growth performance and nutrient digestion in growing livestock [30], but the results were different from the Zadbuke's experiment, where he observed that there were no effects on nitrogen intake, nitrogen retention, and nitrogen balance by feeding a plant mixture in his study [31].…”
Section: N Balance and N Utilization Efficiencysupporting
confidence: 94%
“…In our study, the N intake of sheep in the CD 2% and CD 4% groups was higher than that in the control group, and N egestion in feces had no significant difference between addition groups and control group, indicating higher N digestibility in the CD 2% and CD 4% groups compared with that in the control group. The results agree with the previous studies [27], which showed that increased CP intake resulted in enhanced N digestibility and elevated urinary N excretion in sheep [28], and this may be explained the hydrolysis of plant additives in rumen and reduced complex formation with protein, resulting in increased nitrogen through urine [29]. Retained nitrogen had an increasing tendency in C. deserticola addition group, so during the experimental period, sheep in all addition groups were in positive nitrogen balance; these results were the same as the studies on the impact of phytogenic feed additives on growth performance and nutrient digestion in growing livestock [30], but the results were different from the Zadbuke's experiment, where he observed that there were no effects on nitrogen intake, nitrogen retention, and nitrogen balance by feeding a plant mixture in his study [31].…”
Section: N Balance and N Utilization Efficiencysupporting
confidence: 94%
“…The lower rumen pH might be associated with the higher total VFA concentration. Various reports have verified that rumen NH 3 concentration was influenced by dietary CP intake (Alam et al, 2010;Freeman, Galyean, & Caton, 1992;Haaland, Tyrrell, Moe, & Wheeler, 1982), which is in accordance with our present study.…”
Section: Ruminal Fermentation Characteristicssupporting
confidence: 93%
“…N excretion through faeces was lower, which resulted in a higher N digestibility for the CHM-diet compared with the MHdiet. Previous findings (Alam, Ogata, Sako, Al-Mamun, & Sano, 2010;Al-Mamun et al, 2008;Sano, Kajita, & Fujita, 2004) showed that increased dietary CP intake could enhance N digestibility and urinary N excretion in sheep. In the current experiment, although the N intake was significantly different between diets, the numerical values were very close (1.07 for the MH-diet and 1.09 for the CHM-diet), which seems insufficient to influence N digestibility.…”
Section: N Balancementioning
confidence: 91%
“…The economic point of view and sustainable environmental concerns encourage investigating the possibility of using the crop residue as animal feed. Rice straw is abundantly available crop residues in most tropical and sub-tropical countries and commonly used as a diet for ruminants, although it is low crude protein (CP) content and fermented poorly in the rumen ( Alam et. al., 2010 ; Sarnklong et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%